2023
DOI: 10.1039/d3ra01665j
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive nanofibrous membrane with temperature monitoring for wound healing

Abstract: Developing functional dressings for promoting cellular activities and monitoring the healing progress is receiving increasingly widespread attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Although triboelectric materials can generate electrical stimulation for effective antiviral filtration, the generation of electrical stimulation is often limited by external deformation. Compared with triboelectric materials, microbatteries can be activated by moisture, generating electrical stimulation without relying on mechanical distortion. A range of moisture-induced microbattery-based filters has been developed for antiviral air filtration (Table ).…”
Section: Electroactive Materials For Preventing Virus Infections In F...mentioning
confidence: 99%
“…Although triboelectric materials can generate electrical stimulation for effective antiviral filtration, the generation of electrical stimulation is often limited by external deformation. Compared with triboelectric materials, microbatteries can be activated by moisture, generating electrical stimulation without relying on mechanical distortion. A range of moisture-induced microbattery-based filters has been developed for antiviral air filtration (Table ).…”
Section: Electroactive Materials For Preventing Virus Infections In F...mentioning
confidence: 99%
“…15−18 Using external electrical stimulation to amplify and enhance endogenous electrical signals can effectively promote wound healing. 19−24 Yang et al 19 sputtered Ag/Zn electrodes onto the surface of the PLA nanofiber membrane using electrical stimulation to enhance wound re-epithelialization while monitoring wound temperature to provide timely feedback on wound status. Studies indicated that electrical stimulation therapy was largely limited by battery life or power line constraints.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, bacterial infection, bleeding, and other factors can weaken or abolish the EF strength, resulting in insufficient activation of cell behavior and prolonged nonhealing of the wound. Using external electrical stimulation to amplify and enhance endogenous electrical signals can effectively promote wound healing. Yang et al sputtered Ag/Zn electrodes onto the surface of the PLA nanofiber membrane using electrical stimulation to enhance wound re-epithelialization while monitoring wound temperature to provide timely feedback on wound status. Studies indicated that electrical stimulation therapy was largely limited by battery life or power line constraints. Thus, self-powered wound dressings hold significant promise in providing a convenient and flexible means for effective wound healing.…”
Section: Introductionmentioning
confidence: 99%